Active Learning for Applied Strength of Materials Course: Evidence from NTTU - Chau Thi Than; Ly Thanh Hung; Nguyen Huu Tho; Ihwan Ghazali (Engineering Science Letter, 2022)
In the process of teaching Strength of Materials, students often find it difficult to understand and the level of achievement of the course learning outcomes is not high. Therefore, active teaching methods and application of computer aim to support students actively, proactively, and in project-based learning. This article presents the possibility of integrating the Mdsolids software in teaching strength of materials at Nguyen Tat Thanh University (NTTU) for students majoring in automotive engineering technology. The student satisfaction survey on the course and the application of Mdsolids in teaching were conducted and evaluated to test the effectiveness of active learning activities. The obtained results confirmed further evidence of the benefits of Mdsolids in supporting students to achieve the course learning outcomes.